1996
DOI: 10.1159/000239458
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative Effects of △<sup>24(25)</sup> Sterol Methyl Transferase Inhibitors on <i>Trypanosoma (Schizotrypanum) cruzi</i>: In vitro and in vivo Studies

Abstract: We have studied the antiproliferative effects of two sterol analogs previously reported as potent inhibitors of Δ24(25) sterol methyl transferase (E.C. 2.1.1.43) of yeasts and fungi on epimastigotes and amastigotes on Trypanosoma (Schizotrypanum) cruzi, the causative agents of Chagas disease, as well as its chemotherapeutic effecs in a murine model of the disease. On the epimastigote form proliferating in liver infusion tryptose medium at 28 C 22,26-azasterol (AZA), a cholestanol analog with a 6-mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
88
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(105 citation statements)
references
References 27 publications
15
88
0
2
Order By: Relevance
“…and given daily for 28 consecutive days followed by a 7-day rest and another 15 days of treatment, for a total of 43 doses. This course of treatment was used in our previous studies that first demonstrated the in vivo trypanocidal effects of both D0870 and SCH 56592 (13,16,(32)(33)(34)(35). In addition, other T. cruzi strains (SC-28 and VL-10, both nifurtimox and benznidazole resistant [10]) were included in the study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…and given daily for 28 consecutive days followed by a 7-day rest and another 15 days of treatment, for a total of 43 doses. This course of treatment was used in our previous studies that first demonstrated the in vivo trypanocidal effects of both D0870 and SCH 56592 (13,16,(32)(33)(34)(35). In addition, other T. cruzi strains (SC-28 and VL-10, both nifurtimox and benznidazole resistant [10]) were included in the study.…”
Section: Resultsmentioning
confidence: 99%
“…In a second study, normal (immunocompetent) animals were infected with the same inoculum (10 4 ) and treatment was started at 4 days p.i. but given daily for 28 days, followed by a 7-day rest and another 15 days of treatment (16,29,(32)(33)(34)(35). Surviving animals were monitored for up to 113 days p.i.…”
Section: Parasitesmentioning
confidence: 99%
“…Sterol biosynthesis inhibitors (SBI) have been found to be particularly useful, as endogenous sterols are essential for survival in these pathogenic organisms; these compounds are in most cases orally active, have broad spectrum of activity and very low toxicity (Ryder & Mieth 1992, Mercer 1993, Vanden Bossche 1995. T. cruzi has also an absolute requirement of specific endogenous sterols for cell viability and proliferation and is extremely sensitive to sterol biosynthesis inhibitors (SBI) in vitro (Docampo et al 1981, Beach et al 1986, Goad et al 1989, Urbina et al 1988, 1993, 1996b; thus, the sterol biosynthesis pathway in this organism is a valid chemotherapeutic target (Urbina 1997). Nevertheless, currently available SBI's, such as ketoconazole and itraconazole, have been shown to be unable to eradicate T. cruzi from experimentally infected animals or human patients (McCabe 1988, Moreira et al 1992, Brener et al 1993, although a recent report from Chile claims a high level (>50%) of parasitological cures in chronic patients treated with itraconazole (Apt et al 1998).…”
Section: Parasitological Cure Of Chagas Disease: Is It Possible?mentioning
confidence: 99%
“…1), which has been shown to modify the sterol composition of T. cruzi epimastigotes (the parasite form found in the vector), acting either singly or in combination with other sterol biosynthesis inhibitors (32,37). In addition, the compound also affects amastigotes (13) (the intracellular form of the parasite) and has been shown to have antiproliferative effects in vitro and in vivo (31). Similarly, the compound is active against Leishmania amazonensis promastigotes and amastigotes (24) and Leishmania donovani promastigotes (8).…”
mentioning
confidence: 99%